Copper‐Mediated Halotrifluoromethylation of Unactivated Alkenes. Issue 18 (4th December 2015) - An, Won; Ha, Neul; Lee, Hyun Myung; Malpani, Yashwardhan R.; Lee, Duck‐Hyung; Jung, Young‐Sik; Han, Soo Bong
Abstract: A copper‐mediated halotrifluoromethylation of unactivated alkenes using Umemoto's reagent and copper(I) halide (CuX, X=Cl, Br, and I) was developed. The CuX species (CuI, CuBr, and CuCl) were chosen as the source for both copper and halides because of their benchtop stability, commercial availability, and relatively low cost. Simple exchange of the copper salt provided the desired simultaneous and regioselective incorporation of the halogen atom and of the CF3 group to various alkenes. This protocol offers an efficient and practical route to various β‐halotrifluoromethylated alkanes. Further modifications of the CBr bond to CB, CN and CS bonds were performed. These derivatizations show the feasibility of late‐stage modifications. Abstract :